A synthesis of the evidence on peer-research with potentially vulnerable adults: how this relates to dementia - Di Lorito, Claudio; Birt, Linda; Poland, Fiona; Csipke, Emese; Gove, Dianne; Diaz-Ponce, Ana; Orrell, Martin (Wiley, 2017)
Background. There is limited literature around peer-research in dementia. This study aims to identify the benefits, the risks and the practical challenges and to develop a model of good-practice in peer-research with people with dementia.